Trans-Obturator Approach and the Native Tissue in the Treatment of High Stage Prolapse of the Anterior Vaginal Wall: Midterm Results of a New Surgical Technique - Sharifiaghdas, Farzaneh (Urology Journal, 2020)
Purpose: Pelvic organ prolapse is a common condition as a consequence of the pelvic floor support weakness. This study evaluated the clinical results of treating the high stage prolapse of the anterior vaginal wall using a trans-obturator approach and the native vaginal wall tissue. Methods: This was a prospective analysis of 94 patients with anterior vaginal wall prolapse stage ≥ Ⅲ. They underwent surgery with the trans-obturator approach using the native vaginal wall tissue. The objective primary outcome was evaluated according to the pelvic organ prolapse staging system (POP-Q). The subjective primary outcome was evaluated with pelvic floor distress inventory (PFDI-20) and pelvic floor impact questionnaire (PFIQ-7) questionnaires. The secondary outcomes were post-surgery complications. Results: Totally, 85 of 94 patients were followed up for a mean of 38.2 ± 4 months. The objective anatomical success rate was 90.58%. PDFI-20 and PFIQ-7 scores had improved (P = 0.001). The complications were minor (G1) according to the Clavien-Dindo classification (8.2 %). At one year follow up 3 out of 8 patients with clinical SUI underwent transvaginal repair with the Poly propylene mini sling mesh. Conclusion: The midterm results of the surgical repair of the high stage anterior vaginal wall prolapse are promising with a new surgical technique by trans-obturator approach and native vaginal wall as the supportive layer.